Captain Ben Salomon (1914-1944) - Xavier Riaud (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
Ben Salomon was born in Milwaukee, Wisconsin on September 1, 1914. He graduated from the Dental College of University of South Carolina in 1937 and soon began a dental practice. When the United States entered the war, his patriotic instinct led him to enroll in the army in 1940. After basic training, he joined the 102nd Infantry Regiment and quickly proved to be a natural soldier with weapons and a leader. Within a year, he had risen to the rank of sergeant and was in charge of a machine gun section. In 1942, Salomon was to become an officer in the Dental Corps. He first tried to remain in the infantry, and his commanding officer requested that he be promoted to second lieutenant of infantry: a request which was first denied. It is finally in Hawaii that he was commissioned a first lieutenant on 14 August 1942. After several months working in a hospital, Lieutenant Salomon was assigned in May 1943 as the regimental dental officer of the 105th Infantry Regiment, which was part of the 27th Infantry Division. Even though he had not practiced dentistry for two years, Lieutenant Salomon was quickly recognized as an excellent dentist by his patients and his fellow dentists.